Externalisierung von prozess-spezifischem Mitarbeiterwissen im Produktionsumfeld - Hörner, Lorenz; Schamberger, Markus; Bodendorf, Freimut (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2020)
Using the Example of a Continuous Production Scenario. Shopfloor employees in the manufacturing industry are confronted with increasing requirements on their daily activities. Knowledge about complex production processes is often only available in the employee's minds. To make manufacturing-related knowledge available, a systematic approach to knowledge externalization, storage and reuse is therefore required. Based on a combination and adaptation of different methods, this paper first presents an approach to externalize process-specific employee knowledge. Subsequently, the developed methodology is tested in a continuous manufacturing scenario.<br

Using Tacit Expert Knowledge to Support Shop-floor Operators Through a Knowledge-based Assistance System - Hörner, Lorenz; Schamberger, Markus; Bodendorf, Freimut (Computer Supported Cooperative Work-The Journal of Collaborative Computing, 2022)
The increasing complexity of industrial production systems is challenging employees on the shop-floor in their daily work. Specific knowledge about manufacturing processes is often not available in explicit form but mainly as tacit knowledge of experienced shop-floor workers. A systematic approach to knowledge externalization and reuse is required to make this operational knowledge available. This paper proposes a method to systematically capture and structure expert knowledge while incorporating knowledge management and social research methods. The proposed method's application and evaluation occur in a continuous manufacturing scenario, externalizing tacit knowledge about coping with manufacturing anomalies. A digital assistance system is designed and prototypically implemented to manage and reuse the externalized knowledge. The early involvement of shop-floor workers in the development phase of the prototype ensures usability and user acceptance of the assistance system. The assistance system is developed as a collaboration supporting artifact in the shop-floor's common information space. To observe the resulting productivity performance improvements in the manufacturing scenario, a KPI-based evaluation of the assistance system is presented. Finally, a discussion about the major contributions of this paper, namely the development of an approach for knowledge externalization and a human-centered design of an assistance system, takes place. To assess the novelty of these approaches, they are contrasted with the state of the art identified in the literature before a final summary of the results is presented.
CRIS-Team WoS Importer:2022-09-16